Pleiotropic Roles of a Ribosomal Protein in Dictyostelium discoideum - Amarnath, Smita; Kawli, Trupti; Mohanty, Smita; Srinivasan, Narayanaswamy; Nanjundiah, Vidyanand (PLOS ONE, 2012)
The cell cycle phase at starvation influences post-starvation differentiation and morphogenesis in Dictyostelium discoideum. We found that when expressed in Saccharomyces cerevisiae, a D. discoideum cDNA that encodes the ribosomal protein S4 (DdS4) rescues mutations in the cell cycle genes cdc24, cdc42 and bem1. The products of these genes affect morphogenesis in yeast via a coordinated moulding of the cytoskeleton during bud site selection. D. discoideum cells that over- or under-expressed DdS4 did not show detectable changes in protein synthesis but displayed similar developmental aberrations whose intensity was graded with the extent of over- or under-expression. This suggested that DdS4 might influence morphogenesis via a stoichiometric effect – specifically, by taking part in a multimeric complex similar to the one involving Cdc24p, Cdc42p and Bem1p in yeast. In support of the hypothesis, the S. cerevisiae proteins Cdc24p, Cdc42p and Bem1p as well as their D. discoideum cognates could be co-precipitated with antibodies to DdS4. Computational analysis and mutational studies explained these findings: a C-terminal domain of DdS4 is the functional equivalent of an SH3 domain in the yeast scaffold protein Bem1p that is central to constructing the bud site selection complex. Thus in addition to being part of the ribosome, DdS4 has a second function, also as part of a multi-protein complex. We speculate that the existence of the second role can act as a safeguard against perturbations to ribosome function caused by spontaneous variations in DdS4 levels.